Temporomandibular Joint Pathology Current Approaches and Understanding - Emes, Yusuf; Aybar, Buket; Dergin, Gühan (IntechOpen, 2018)
Dental practitioners face a large number of patients seeking help for pain and loss of function in their temporomandibular joint and related structures. This book consists of eight chapters by authors who would like to share their experiences and researches on pathological conditions related to the temporomandibular joint. The chapters mainly focus on disorders, diseases, and entities while shedding light on the diagnostic methods and management modalities.